(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article presents pedagogical possibilities and their features based on an integrated approach to the study of probability theory and Mathematical Statistics. In school education, the goals and objectives of the study of probabilistic statistical materials have been determined, and a complex organizational structure of the pedagogical possibilities of studying the course has been developed. The components of the complex are aimed at the development of students ’ abilities "logical thinking", "critical thinking", "probabilistic-statistical thinking", cover the possibilities of systematic improvement of the probabilistic-statistical content, training on the basis of mutual internal involvement of mathematics, training opportunities using computer technology and training opportunities in a differentiated educational environment.